Alliance rising - Cherryh, C. J; Fancher, Jane, 1952- (Cherryh, C. J. Hinder stars, 2019)
For years, the stations of the Hinder Stars, those old stations closest to Sol, have lagged behind the great megastations of the Beyond, like Pell and Cyteen. But new opportunities and fears arise when Alpha station receives news of an incoming ship with no identification. The denizens of Alpha wait anxiously for news about the outsiders, each with their own suspicions about the ship and its origins. Ross and Fallon, crew members of the Galway, believe the unidentified ship belongs to Pell and has come to investigate another massive ship docked at Alpha, The Rights of Man. Though Rights is under the command of the Earth Company, it is not quite perfected--and its true purpose is shrouded in mystery. James Robert Neihart, captain of Finity's End--a huge faster-than-light ship flown by one of the Merchanter Families--has heard whispers of The Rights of Man and wonders at its design and purpose, especially as Sol struggles to rival the progress of the Farther Stars. Now docked at Alpha, he must convince the crews that there is more to The Rights of Man than meets the eye. Because the reasons behind the creation of The Rights of Man, and its true plans, could change everything--not just for Sol, but for the Hinder Stars and the Beyond itslf.